Síndrome de Russel ou síndrome de Diencefálica de emagreciemento Russel's syndrome or diencephalic syndrome of emaciation: a case report - Nelson Pires Ferreira; Ércio Amaro de Oliveira (Arquivos de Neuro-Psiquiatria)
Os autores relatam um caso de síndrome de Russel ou síndrome diencefálica do emagrecimento. Revisam a literatura disponível sobre o assunto e comentam a dificuldade do diagnóstico na fase inicial da doença. The case of a four years old patient with Russel syndrome or diencephalic syndrome of emaciation is reported. The literature on the subject is reviewed. The difficulties for the diagnosis at the inicial fase of the illness are discussed.